2009
DOI: 10.1007/s00280-009-1164-9
|View full text |Cite
|
Sign up to set email alerts
|

Early alterations in heart gene expression profiles associated with doxorubicin cardiotoxicity in rats

Abstract: Genomic analysis provided further evidence that mitochondria are the primary target of doxorubicin-induced oxidative damage that leads to cardiomyopathy and the primary site of cardioprotective action by dexrazoxane. Additional strategies that prevent the formation of oxygen radicals by doxorubicin in mitochondria may provide increased cardioprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 33 publications
4
32
1
Order By: Relevance
“…Hence, increased protection against MOMP after DOX exposure, and hence a counter-priming, is indicated by elevation of the anti-apoptotic protein BCL2 [23], by an increase of BCL2/BAX protein ratio [57] and elevation of the anti-apoptotic gene ARC in rat hearts [58,59]. As most of these studies were performed in whole hearts, further studies will reveal to what extent DOX primes or anti-primes cardiomyocytes to further pre-or post-MOMP apoptosis or to apoptosis susceptibility to cell death ligands.…”
Section: Does Dox Exposure Change Apoptosis Likelihood To Later Somatmentioning
confidence: 99%
“…Hence, increased protection against MOMP after DOX exposure, and hence a counter-priming, is indicated by elevation of the anti-apoptotic protein BCL2 [23], by an increase of BCL2/BAX protein ratio [57] and elevation of the anti-apoptotic gene ARC in rat hearts [58,59]. As most of these studies were performed in whole hearts, further studies will reveal to what extent DOX primes or anti-primes cardiomyocytes to further pre-or post-MOMP apoptosis or to apoptosis susceptibility to cell death ligands.…”
Section: Does Dox Exposure Change Apoptosis Likelihood To Later Somatmentioning
confidence: 99%
“…It has also been shown that the use of a conventional cardioprotective agent, such as dexrazoxane, together with chemotherapy, reduces the expression of the NRF-2 gene (responsible for oxidative stress response), which is overexpressed in patients receiving ANT alone (2). We previously identified an epirubicin (EPI)-induced early myocardial dysfunction, detected after a low dose (200 mg/ m 2 ) of EPI (7).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that chemotherapy-induced cardiotoxicity (CTX) produced by ANTs is at least partially mediated by chronic inflammation and oxidative stress, with proinflammatory cytokines, interleukin-6 (IL-6) and tumor necrosis factor (TNF)-α and reactive oxygen species (ROS) (2) playing a central role (5,6). It has also been shown that the use of a conventional cardioprotective agent, such as dexrazoxane, together with chemotherapy, reduces the expression of the NRF-2 gene (responsible for oxidative stress response), which is overexpressed in patients receiving ANT alone (2).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has also been reported that some pathological cardiac dysfunctions such as hypertrophy were associated with the up-regulation of fetal genes such as atrial natriuretic factor (ANF) and isoforms of myosin heavy chain (MHC) (Ritter and Neyses, 2003;van den Bosch et al, 2006). Early alterations in heart gene expression profiles associated with cardiotoxicity have been studied in vitro and in vivo (Thompson et al, 2010). Using microarrays, Berthiaume and Wallace (2007) studied global gene expression changes occurring in rats' hearts 5 weeks after subchronic DOX treatment.…”
Section: Introductionmentioning
confidence: 99%